Addicted? Reduced host resistance in populations with defensive symbionts - Martinez, Julien (Proc Biol Sci, 2016)
Heritable symbionts that protect their hosts from pathogens have been described in a wide range of insect species. By reducing the incidence or severity of infection, these symbionts have the potential to reduce the strength of selection on genes in the insect genome that increase resistance. Therefore, the presence of such symbionts may slow down the evolution of resistance. Here we investigated this idea by exposing Drosophila melanogaster populations to infection with the pathogenic Drosophila C virus (DCV) in the presence or absence of Wolbachia, a heritable symbiont of arthropods that confers protection against viruses. After nine generations of selection, we found that resistance to DCV had increased in all populations. However, in the presence of Wolbachia the resistant allele of pastrel—a gene that has a major effect on resistance to DCV—was at a lower frequency than in the symbiont-free populations. This finding suggests that defensive symbionts have the potential to hamper the evolution of insect resistance genes, potentially leading to a state of evolutionary addiction where the genetically susceptible insect host mostly relies on its symbiont to fight pathogens.